8 - Prosecuting International Crimes in Africa: Lessons from Rwanda and Reflections on the Future - Jallow, Hassan B. (Africa Development, 2021)
In this article the former Chief Prosecutor of the International Criminal Tribunal for Rwanda reflects on his experiences to respond to the question: what options are available for Africa in dealing with mass atrocity crimes based on the ICTR experience? The article notes the pedigree of Africa in terms of international criminal justice and the contributions this allows it to bring to the broad questions of ensuring justice for mass atrocities and building peace and reconciliation after such incidences.